Genome–Wide Hypomethylation and Specific Tumor-Related Gene Hypermethylation are Associated with Esophageal Squamous Cell Carcinoma Outcome. Issue 3 (March 2015) - Hoshimoto, Sojun; Takeuchi, Hiroya; Ono, Shigeshi; Sim, Myung Shin; Huynh, Jamie L.; Huang, Sharon K.; Marzese, Diego M.; Kitagawa, Yuko; Hoon, Dave S. B.
Abstract : Introduction: Esophageal squamous cell carcinoma (ESCC) is a cancer of variable outcomes with limited effective treatments resulting in poor overall survival (OS). Epigenetic alterations contributing to this deadly cancer type that can be used as novel therapeutic or diagnostic targets are still poorly understood. Methods: We explored genome-wide DNA methylation data from The Cancer Genome Atlas project and identified a panel of tumor-related genes hypermethylated in ESCC. The methylation statuses of RASSF1, RARB, CDKN2A (p16INK4a, p14ARF), APC, and RUNX3 genes and long interspersed nucleotide element-1 (LINE-1) were validated in a large cohort ( n = 140) of clinically well-annotated ESCC specimens and esophageal normal mucosa ( n = 28) using a quantitative methylation-specific polymerase chain reaction. Results: Hypermethylation of RARB, p16INK4a, RASSF1, APC, RUNX3, and p14ARF were observed in 55%, 24%, 20%, 19%, 14%, and 8% of specimens, respectively. Hypermethylation of APC was significantly associated with tumor depth ( p = 0.02) and American Joint Committee on Cancer stage ( p = 0.03). Global DNA methylation level, assessed by LINE-1, was significantly lower in ESCC than in normal mucosa ( p < 0.0001), and lower in greater than or equal to T2 ( n = 69) than T1 tumors ( n = 45; p = 0.03). There was a significant inverse correlation between LINE-1 and RARB methylation ( p = 0.008). Importantly, hypermethylation of RASSF1 and APC genes was significantly associated with overall survival (OS; p = 0.006 and p = 0.007, respectively). In addition, patients with tumors containing a higher number of methylated genes (greater than two genes) presented worse OS ( p = 0.003). Conclusions: This study demonstrates that epigenetic alterations of a panel of tumor-related genes and the noncoding region LINE-1 can be used as prognostic indicators and help in clinical management of ESCC patients.